Jahresbericht 2000 : die vorteile der weltwirtschaft fur alle sichern. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Annual Report of the Executive Board for the financial year ended April 30, 2000.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet